Housing, consumption and monetary policy: how different are the US and the euro area? - Alberto Musso; Stefano Neri; Livio Stracca (European Central Bank (ECB), 2010)
The paper provides a systematic empirical analysis of the role of the housing market in the macroeconomy in the US and in the euro area. First, it establishes some stylised facts concerning key variables in the housing market, such as the real house price, residential investment and mortgage debt on the two sides of the Atlantic. Then, it presents evidence from Structural Vector Autoregressions (SVAR) by focusing on the effects of three structural shocks, (i) monetary policy, (ii) credit supply and (iii) housing demand shocks on the housing market and the broader economy. We find that similarities overshadow dierences as far as the role of the housing market is concerned. We find evidence pointing in the direction of a stronger role for housing in the transmission of monetary policy shocks in the US, while the evidence is less clearcut for housing demand shocks. We also find that credit supply shocks matter more in the euro area.
Keywords: E22; E44; E52; 330; credit; House prices; monetary policy; Residential investment; Wohneigentum; Immobilienpreis; Hypothek; Geldpolitik; Schock; VAR-Modell; Eurozone; EU-Staaten; USA